HUBUNGAN MINAT BELAJAR KEJURUAN DAN PRESTASI BELAJAR KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA PADA SISWA KELAS XI JURUSAN TEKNIK PEMESINAN SMK KRISTEN 1 KLATEN TAHUN AJARAN 2014/2015 - Syahrul Yusliyantoro; Samidjo Samidjo (Jurnal Taman Vokasi, 2017)
This study aims to determine how much (1) the correlation  vocational of learning interest and entrepreneurship learning achievement to entrepreneurship interest, (2) the correlation between  vocational learning interest and  entrepreneurship interest  and (3) the correlation  between learning achievement entrepreneurship with entrepreneurship interest  of the grade XI student of  technical machine  SMK  Christian 1 Klaten Academic in academic  Year 2014/2015.This study is an ex-post facto. The population in this study is all students of grade XI technical machine as 68 students. This data collection techniques using questionnaires and documentation. A test instrument using validity and reliability test item instrument. The analyzed technique  using descriptive and analytical prerequisite test that includes tests of normality, linearity and multicollinearity test. Data analysis using partial correlation and multiple regression and analyzed with SPSS 21,00.This research includes that there is a positive significant correlation  between vocational  learning interest and  entrepreneurship interest,  there is a significant positive correlation between entrepreneurship learning achievement with  entrepreneurship internet , and there is a significant positive correlation  between vocational learning interest and entrepreneurship learning achievement with entrepreneurship interest.